Quantitative changes of the alkaloid complex in a submerged culture of Claviceps paspali - Ricicová, A; Flieger, M; Rehácek, Z (Folia microbiologica, 1982)
Claviceps paspali FA produced high concentrations of alkaloid under submerged conditions. Their production was found to depend on the developmental stage and treatment of the filamentous culture inoculum. A medium containing Bacto-peptone with a constant composition of amino acids was selected for the preparation of the inoculum. A two-week fermentation in a synthetic medium with mannitol at 24 +/- 1 degrees C resulted in an increased production of total alkaloids from the original value of 100-200 micrograms/mL to more than 2000 micrograms/mL. Addition of tryptophan did not further increase the production of alkaloids but resulted in changes of the spectrum of some metabolites, 2,3-Dihydroxybenzoic acid accompanied the alkaloids in the fermentation medium. alpha-Hydroxyethyllysergamide was the predominant component of extracellular alkaloids (80% in the first days of fermentation). During fermentation the level of this alkaloid continuously decreased while the concentration of the accompanying alkaloids, i.e. lysergamide and the corresponding minor isomers, increased.
Keywords: Culture Media; Claviceps; Fermentation; Tryptophan; kyselina lysergová; glukosa; Glucose; tryptofan; Alkaloids; Lysergic Acid; Mannitol; mannitol; fermentace; alkaloidy; kultivační média